Integrasi Smart Water Management Berbasis Kearifan Lokal Sebagai Upaya Konservasi Sumber Daya Air di Indonesia (Indonesian Journal of Conservation, 2021)
Information and communication technology (ICT) is useful as an effort to conserve water resources to improve the quality of higher management, or Smart Water Management (SWM). SWM is an ICT optimization that provides automatic real-time information on environmental conditions and water resources, as well as estimates of meteorological and climatic conditions, in order to solve problems related to water resource conservation. The purpose of this article is to analyze how the concept of Smart Water Management (SWM) is based on local wisdom as an effort to conserve Water Resources in Indonesia. This article is an integrator writing audit with subjective graphics based on a writing survey based on a systematic literature review (SLR). The literature search was carried out online on the Google Scholar database using the Publish or Perish software with restrictions for 2016-2021 with the keywords “Smart Water Management”, “Conservation”, “Local Wisdom” and “Water Resources”. (1) analyzing the management concept of sustainable water resources conservation, (2) describing local wisdom in water resources conservation efforts, in Indonesia, (3) implementing local wisdom-based SWM as an effort to conserve water resources, (4) presenting conclusions. The results of the analysis of various articles show that Indonesia has a lot of local wisdom in efforts to conserve natural resources in the community. The SWM concept has not been fully implemented in the management of natural resources, which exist in the community. The existence of this SWM concept can be integrated with local community wisdom, in an effort to conserve water resources, in Indonesia. So that it can increase the effectiveness and efficiency of natural resource management so that natural resource conservation efforts can be carried out more optimally and sustainably so that it can predict future water needs.